Before School Education In The Institution Football Lessons Organization Reach Methodology (Eurasian Journal of Humanities and Social Sciences, 2025)
In the article current on the day in our homeland current become standing football develop issue on the surface measures performance provide in the purpose for preschoolers to teach the elements of football done more effective for increasing football in preschools to teach methodology about word carried out. For children football in teaching what for more attention to give and training organization to grow according to advice and instructions giving passed .